The Image of the Muslim Woman in Western Thought - Klaina, Mekki (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study explores the depiction of Muslim women in Western thought, critically analyzing the entrenched stereotypes and biases. It specifically addresses three prevalent allegations: the supposed oppression of women via Islamic dress codes, incidents of violence against women in Islamic contexts, and alleged discrimination between genders under Islamic law. Utilizing a critical analytical method, the research juxtaposes Islamic teachings with Western criticisms using both Islamic and Western references. Findings indicate that Western portrayals of Muslim women often lack depth and fail to consider the socio-religious contexts of Islamic practices. For example, while the hijab is portrayed in the West as a symbol of oppression, it is often embraced by Muslim women as a mark of modesty and dignity. The study also points out that issues like domestic violence and gender discrimination are globally prevalent and not exclusive to Islamic societies. It concludes that critiques grounded in Western secular and modernist values without an understanding of the Islamic perspective lead to distorted views of Islam. This research aims to bridge understanding and foster dialogue between Western and Islamic perspectives on women's rights and status, suggesting that while some areas in Muslim societies need reform, the overarching Western critique may not fully grasp the nuanced realities of Muslim women's lives.